Method for converting waste plastics into high-value MOF (Metal Organic Framework) material based on continuous process

By using a continuous process method in recycling of waste PET plastics, PET powder reacts with components such as betaine, glycol and sodium hydroxide to form high-performance MOF materials, solving the problem of recycling and treatment of waste PET plastics. Efficient and low-cost resource utilization has been achieved.

CN119431819APending Publication Date: 2025-02-14ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411828857.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively recycle and deal with waste PET plastics. The traditional methods have problems of environmental pollution, health risks and high costs. At the same time, the existing methods converted to MOF products have poor performance and are difficult to meet the actual application needs.

Method used

Using a continuous process method, the PET powder is mixed with the weakly basic catalyst betaine and ethylene glycol, and after heating, sodium hydroxide and metal salt solution are added to form a MOF material by stirring reaction.

Benefits of technology

The synthesis of high-quality MOF materials has been achieved. The material has excellent porous structure, uniform pores and large specific surface area, which meets the needs of high-performance MOFs and provides a high-value resource utilization solution for waste PET plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431819A_ABST
    Figure CN119431819A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste plastic recycling, and discloses a method for converting waste plastic into a high-value MOF material based on a continuous process. The method comprises the following steps: firstly, crushing the waste PET plastic, mixing the crushed waste PET plastic with betaine, and carrying out a heating reaction in ethylene glycol to form a ligand carrier solution; then, alkaline earth metal salt is dissolved in dimethylformamide (DMF) to prepare a metal salt solution, sodium hydroxide (NaOH) is added into the ligand carrier solution at the temperature of 110-130 DEG C, and a turbid ligand salt solution is formed; then, adding the metal salt solution into the ligand salt, and promoting a coordination reaction to obtain a solid-liquid mixture; finally, the MOF material with excellent performance is prepared through the steps of washing, drying and the like. The obtained MOF material has a uniform porous structure and a relatively large specific surface area, and shows a wide potential of high-value utilization of waste PET plastic resource. The method is simple in process and suitable for industrial continuous production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycling waste plastics, and in particular to a method for converting waste plastics into high-value MOF materials based on a continuous process. Background Art

[0002] Polyethylene terephthalate (PET) is a widely used thermoplastic polymer with the advantages of high strength, high temperature resistance and good stability. It is often used in the production of soft drink bottles, food packaging and textile fibers, and is the fourth largest plastic in the world. However, PET-based products usually have a short life cycle, and its waste cannot be degraded in nature, causing serious environmental pollution.

[0003] How to effectively treat and recycle waste PET plastics has become a global problem that needs to be solved urgently. Traditional plastic disposal methods such as landfill and incineration often cause soil pollution, water pollution and health risks, and plastic waste continues to accumulate, wasting a lot of carbon resources. Existing plastic recycling technologies, such as mechanical recycling, are difficult to achieve effective recycling due to high costs, mechanical performance degradation and unstable product quality. Therefore, finding an efficient, low-cost and environmentally friendly method for the treatment of waste plastics is a key issue that needs to be solved urgently.

[0004] Metal-organic framework (MOF) materials are a type of porous crystalline material with a regular network structure formed by metal ions as central nodes and connected by organic ligands. MOF has shown great application potential in gas storage, gas separation, catalysis, sensors and biomedicine due to its adjustable structure, high porosity and large specific surface area. In recent years, the use of waste PET plastic as a precursor of terephthalic acid for MOF synthesis can realize the green resource utilization of plastic waste, which is in line with the concept of circular economy and has good environmental and economic benefits.

[0005] At present, there are many methods for converting waste PET into MOF materials, mainly including solvothermal method and ball milling method. Although the solvothermal method can produce high-performance MOF materials, it usually requires a large amount of organic solvents, high temperature and high pressure conditions, long reaction time, high energy consumption, and serious environmental pollution. The mechanical ball milling method has attracted attention for its green and efficient characteristics, but the MOF materials synthesized by this method usually have a low specific surface area and poor crystal structure, which is difficult to meet the needs of practical applications.

[0006] For example, the patent with application publication number CN115716918A discloses a method for preparing metal-organic framework materials by ball milling-solution blending. The method converts waste PET into MOF by ball milling solution blending, wherein PET is ball milled with a strong base compound to obtain a degradation product, terephthalate, and then the degradation product is dissolved in water, and a metal salt aqueous solution is dripped into the terephthalate aqueous solution, stirred to form a precipitate, and the MOF material is obtained after washing and drying. However, the specific surface area of ​​the MOF material prepared by this method is less than 100m² / g, which is difficult to meet the requirements of high-performance MOF. For another example, the patent with application publication number CN115678030A discloses a method for preparing MOF by two-step ball milling, wherein PET is ball milled with sodium hydroxide to generate sodium terephthalate and ethylene glycol, and then a metal salt is added to continue ball milling, and the metal ions are coordinated with the terephthalate ions under the action of mechanical force to form MOF. However, the MOF synthesized by this method has a poor crystal structure and a specific surface area of ​​less than 150m² / g, and its practical application prospects are limited.

[0007] In summary, for the conversion of waste PET into MOF, it is urgent to develop a new and efficient conversion method to increase the added value of the conversion products and meet the needs of practical applications in this field. Summary of the invention

[0008] In order to solve the above-mentioned technical problem of converting waste PET into MOF, the present invention provides a method for converting waste plastics into high-value MOF materials based on a continuous process.

[0009] The specific technical scheme of the present invention is: In one aspect, the present invention provides a method for converting waste plastics into high-value MOF materials based on a continuous process, comprising the following steps: PET powder, weak alkaline catalyst and ethylene glycol are mixed and heated to obtain a clear solution, then cooled to 110-130°C, sodium hydroxide is added, stirred for a primary reaction, and then a metal salt solution is added for a secondary reaction to obtain MOF material.

[0010] Preferably, the mass ratio of PET powder to ethylene glycol is 1:4-10.

[0011] Preferably, the catalyst is a weakly alkaline catalyst.

[0012] More preferably, the catalyst is betaine.

[0013] More preferably, the mass ratio of PET powder to betaine is 10-20:1.

[0014] Preferably, the heating temperature is 190-200° C., and the heating time is 2-4 hours.

[0015] Preferably, the molar ratio of PET powder to sodium hydroxide is 1:2-4.

[0016] Preferably, the stirring rate of the primary reaction is 300-800 r / min, and the time of the primary reaction is 30-60 min.

[0017] Preferably, the metal salt is selected from alkaline earth metal salts.

[0018] More preferably, the metal salt is selected from one or more of cobalt nitrate, nickel nitrate, zinc nitrate and calcium chloride.

[0019] Preferably, the stirring rate of the secondary reaction is 300-800 r / min, and the time of the secondary reaction is 4-12 hours.

[0020] On the other hand, based on the above method, the present invention provides a method for recycling waste plastics and provides the application of the above method in processing recycled plastics.

[0021] Compared with the prior art, the present invention has the following technical effects: 1. The method of the present invention first crushes the waste PET and mixes it with a weak alkaline catalyst betaine, and heats it in ethylene glycol to react to form a ligand carrier solution; then, the alkaline earth metal salt is dissolved in DMF to prepare a metal salt solution, and NaOH is added to the ligand solution at 110-130°C to make it turbid to form a ligand salt; then, the metal salt solution is added to the ligand salt to react, and finally a solid-liquid mixture is obtained, and a MOF material is obtained after washing and drying. The material has an excellent porous structure, uniform pores, and a large specific surface area, showing the potential for converting waste PET plastics into beneficial resources.

[0022] 2. The results of the present invention prove that the addition amount of betaine, alkaline earth metal salt and sodium hydroxide plays a vital role in the synthesis of MOF materials. By controlling the amount of the three components, high-quality MOF materials can be effectively synthesized, among which the specific surface area of ​​the synthesized MOF material can reach up to 428 m 2 / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of Co-BDC prepared in Example 1 of the present invention; Figure 2 is the X-ray diffraction spectrum of Co-BDC prepared in Example 1 of the present invention; Figure 3 is a SEM image of the Ni-BDC prepared in Example 4 of the present invention; Figure 4is the X-ray diffraction spectrum of Ni-BDC prepared in Example 4 of the present invention; Figure 5 is a SEM image of the Zn-BDC prepared in Example 5 of the present invention; Figure 6 is the X-ray diffraction spectrum of Zn-BDC prepared in Example 5 of the present invention; Figure 7 is a SEM image of the Ca-BDC prepared in Example 6 of the present invention; Figure 8 This is the X-ray diffraction spectrum of Ca-BDC prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.

[0025] Example 1 A method for converting waste plastics into high-value MOF materials based on a continuous process is provided, comprising the following steps: (1) PET waste plastic was crushed into powder to obtain PET powder. 4 g PET powder and 0.2 g betaine were mixed evenly and added to 16 g ethylene glycol solvent. The system was heated to 200 °C and reacted by magnetic stirring at a stirring rate of 400 r / min. After stirring for 2 h, the system became a clear solution, and a ligand carrier solution was obtained.

[0026] (2) Weigh 0.0328 mol of cobalt nitrate and add it to 20 g of DMF solvent. Dissolve it by magnetic stirring to obtain a metal salt solution.

[0027] (3) The temperature of the ligand carrier solution was lowered to 130°C, 0.0328 mol NaOH was added, and the reaction was carried out for 30 min until the solution became turbid to obtain a ligand salt solution. The metal salt solution was then added to the ligand salt solution, and the reaction was stirred for 4 h at a stirring rate of 400 r / min.

[0028] (4) The solid-liquid mixture obtained by the above reaction was poured into a Buchner funnel and repeatedly washed with ethanol and water as solvents for 6 times to eliminate impurities in the preparation process; and then dried to obtain a MOF material, which was recorded as Co-BDC material.

[0029] The Co-BDC material obtained in this example was analyzed by scanning electron microscope and X-ray diffraction. Figure 1 and Figure 2 .

[0030] Figure 1 This is a scanning electron microscope image of the Co-BDC material of this embodiment. Figure 2 The X-ray diffraction spectrum of the Co-BDC material of this embodiment. From the scanning electron microscope image, it can be seen that the morphology of the Co-BDC material is a nano-petal-like structure with uniform pores and a large specific surface area. From the X-ray powder diffraction spectrum, it can be seen that the Co-BDC material has a significant characteristic diffraction peak, indicating that the Co-BDC material was successfully synthesized.

[0031] Example 2 A method for converting waste plastics into high-value MOF materials based on a continuous process is provided, comprising the following steps: (1) PET waste plastic was crushed into powder to obtain PET powder. 2.5 g PET powder and 0.25 g betaine were mixed evenly and added to 25 g ethylene glycol solvent. The system was heated to 200 °C and reacted by magnetic stirring at a stirring rate of 800 r / min. After stirring for 2 h, the system became a clear solution, thereby obtaining a ligand carrier solution.

[0032] (2) Weigh 0.041 mol of cobalt nitrate and add it to 20 g of DMF solvent. Dissolve it by magnetic stirring to obtain a metal salt solution.

[0033] (3) The temperature of the ligand carrier solution was lowered to 130°C, 0.041 mol NaOH was added, and the reaction was continued for 30 min until the solution became turbid to obtain a ligand salt solution. The metal salt solution was then added to the ligand salt solution, and the reaction was stirred for 4 h at a stirring rate of 800 r / min.

[0034] (4) The solid-liquid mixture obtained by the above reaction was poured into a Buchner funnel and repeatedly washed with ethanol and water as solvents for 6 times to eliminate impurities in the preparation process; and then dried to obtain a MOF material, which was recorded as Co-BDC material.

[0035] The Co-BDC material obtained in this example was subjected to a scanning electron microscope and an X-ray diffraction analysis was performed. The results showed that the Co-BDC material prepared in this example had significant characteristic diffraction peaks, and the Co-BDC material was successfully synthesized.

[0036] Example 3 A method for converting waste plastics into high-value MOF materials based on a continuous process is provided, comprising the following steps: (1) PET waste plastic was crushed into powder to obtain PET powder. 1 g of PET powder and 0.05 g of betaine were mixed evenly and added to 4 g of ethylene glycol solvent. The system was heated to 200 °C and reacted by magnetic stirring at a stirring rate of 300 r / min. After stirring for 2 h, the system became a clear solution, and a ligand carrier solution was obtained.

[0037] (2) Weigh 0.0082 mol of cobalt nitrate and add it to 20 g of DMF solvent. Dissolve it by magnetic stirring to obtain a metal salt solution.

[0038] (3) The temperature of the ligand carrier solution was lowered to 130°C, 0.0082 mol NaOH was added, and the reaction was continued for 30 min until the solution became turbid to obtain a ligand salt solution. The metal salt solution was then added to the ligand salt solution, and the reaction was stirred for 4 h at a stirring rate of 300 r / min.

[0039] (4) The solid-liquid mixture obtained by the above reaction was poured into a Buchner funnel and repeatedly washed with ethanol and water as solvents for 6 times to eliminate impurities in the preparation process; and then dried to obtain a MOF material, which was recorded as Co-BDC material.

[0040] The Co-BDC material obtained in this example was subjected to a scanning electron microscope and an X-ray diffraction analysis was performed. The results showed that the Co-BDC material prepared in this example had significant characteristic diffraction peaks, and the Co-BDC material was successfully synthesized.

[0041] Example 4 A method for converting waste plastics into high-value MOF materials based on a continuous process is provided, which is mainly different from Example 1 in that: in step (2), nickel nitrate is added to prepare a metal salt solution. The other steps are the same as those in Example 1.

[0042] The method of this embodiment includes the following steps: (1) PET waste plastic was crushed into powder to obtain PET powder. 4 g PET powder and 0.2 g betaine were mixed evenly and added to 16 g ethylene glycol solvent. The system was heated to 200 °C and reacted by magnetic stirring at a stirring rate of 400 r / min. After stirring for 2 h, the system became a clear solution, and a ligand carrier solution was obtained.

[0043] (2) Weigh 0.0328 mol of nickel nitrate and add it to 20 g of DMF solvent. Dissolve it by magnetic stirring to obtain a metal salt solution.

[0044] (3) The temperature of the ligand carrier solution was lowered to 130°C, 0.0328 mol NaOH was added, and the reaction was carried out for 30 min until the solution became turbid to obtain a ligand salt solution. The metal salt solution was then added to the ligand salt solution, and the reaction was stirred for 4 h at a stirring rate of 400 r / min.

[0045] (4) The solid-liquid mixture obtained by the above reaction was poured into a Buchner funnel and repeatedly washed with ethanol and water as solvents for 6 times to eliminate impurities in the preparation process; and then dried to obtain a MOF material, which was recorded as Ni-BDC material.

[0046] The Ni-BDC material obtained in this example was analyzed by scanning electron microscope and X-ray diffraction. Figure 3 and Figure 4 .

[0047] Figure 3 This is a scanning electron microscope image of the Ni-BDC material of this embodiment. Figure 4 The X-ray diffraction spectrum of the Ni-BDC material of this embodiment. From the scanning electron microscope image, it can be seen that the morphology of the Ni-BDC material is a foam structure with uniform pores. From the X-ray powder diffraction spectrum, it can be seen that the Ni-BDC material has significant characteristic diffraction peaks, indicating that the Ni-BDC material was successfully synthesized.

[0048] Example 5 A method for converting waste plastics into high-value MOF materials based on a continuous process is provided, which is mainly different from Example 1 in that: in step (2), zinc nitrate is added to prepare a metal salt solution. The other steps are the same as those in Example 1.

[0049] The method of this embodiment includes the following steps: (1) PET waste plastic was crushed into powder to obtain PET powder. 4 g PET powder and 0.2 g betaine were mixed evenly and added to 16 g ethylene glycol solvent. The system was heated to 200 °C and reacted by magnetic stirring at a stirring rate of 400 r / min. After stirring for 2 h, the system became a clear solution, and a ligand carrier solution was obtained.

[0050] (2) Weigh 0.0328 mol of zinc nitrate and add it to 20 g of DMF solution. Dissolve it by magnetic stirring to obtain a metal salt solution.

[0051] (3) The temperature of the ligand carrier solution was lowered to 130°C, 0.0328 mol NaOH was added, and the reaction was carried out for 30 min until the solution became turbid to obtain a ligand salt solution. The metal salt solution was then added to the ligand salt solution, and the reaction was stirred for 4 h at a stirring rate of 400 r / min.

[0052] (4) The solid-liquid mixture obtained by the above reaction was poured into a Buchner funnel and repeatedly washed with ethanol and water as solvents for 6 times to eliminate impurities in the preparation process; and then dried to obtain a MOF material, which was recorded as Zn-BDC material.

[0053] The Zn-BDC material obtained in this example was analyzed by scanning electron microscope and X-ray diffraction. Figure 5 and Figure 6 .

[0054] Figure 5 This is a scanning electron microscope image of the Zn-BDC material of this embodiment. Figure 6 The X-ray diffraction spectrum of the Zn-BDC material of this embodiment. The morphology of the Zn-BDC material can be seen from the scanning electron microscope image. From the X-ray powder diffraction spectrum, it can be seen that the Zn-BDC material has significant characteristic diffraction peaks, indicating that the Zn-BDC material was successfully synthesized.

[0055] Example 6 A method for converting waste plastics into high-value MOF materials based on a continuous process is provided, which is mainly different from Example 1 in that: in step (2), calcium chloride is added to prepare a metal salt solution. The other steps are the same as in Example 1.

[0056] The method of this embodiment includes the following steps: (1) PET waste plastic was crushed into powder to obtain PET powder. 4 g PET powder and 0.2 g betaine were mixed evenly and added to 16 g ethylene glycol solvent. The system was heated to 200 °C and reacted by magnetic stirring at a stirring rate of 400 r / min. After stirring for 2 h, the system became a clear solution, and a ligand carrier solution was obtained.

[0057] (2) Weigh 0.0328 mol of calcium chloride and add it to 20 g of DMF solution. Dissolve it by magnetic stirring to obtain a metal salt solution.

[0058] (3) The temperature of the ligand carrier solution was lowered to 130°C, 0.0328 mol NaOH was added, and the reaction was carried out for 30 min until the solution became turbid to obtain a ligand salt solution. The metal salt solution was then added to the ligand salt solution, and the reaction was stirred for 4 h at a stirring rate of 400 r / min.

[0059] (4) The solid-liquid mixture obtained by the above reaction was poured into a Buchner funnel and repeatedly washed with ethanol and water as solvents for 6 times to eliminate impurities in the preparation process; and then dried to obtain a MOF material, which was recorded as Ca-BDC material.

[0060] The Ca-BDC material obtained in this example was analyzed by scanning electron microscope and X-ray diffraction. Figure 7 and Figure 8 .

[0061] Figure 7 This is a scanning electron microscope image of the Ca-BDC material of this embodiment. Figure 8 The X-ray diffraction spectrum of the Ca-BDC material of this embodiment is shown in Figure 1. The morphology of the Ca-BDC material can be seen from the scanning electron microscope image. From the X-ray powder diffraction spectrum, it can be seen that the Ca-BDC material has significant characteristic diffraction peaks, indicating that the Ca-BDC material was successfully synthesized.

[0062] Comparative Example 1 This comparative example aims to study the effect of the amount of betaine added in step (1) on the synthesis of MOF materials.

[0063] The main difference between this comparative example and Example 1 is that the amount of betaine added in step (1) is 0.08 g. The rest is the same as Example 1.

[0064] Comparative Example 2 This comparative example aims to study the effect of the amount of betaine added in step (1) on the synthesis of MOF materials.

[0065] The main difference between this comparative example and Example 1 is that the amount of betaine added in step (1) is 1 g. The rest is the same as in Experimental Example 1.

[0066] Comparative Example 3 This comparative example aims to study the effect of the amount of alkaline earth metal salt added in step (2) on the synthesis of MOF materials.

[0067] The main difference between this comparative example and Example 1 is that the amount of metal salt added in step (2) is 0.082 mol. The rest is the same as that in Experimental Example 1.

[0068] Comparative Example 4 This comparative example aims to study the effect of the amount of alkaline earth metal salt added in step (2) on the synthesis of MOF materials.

[0069] The main difference between this comparative example and Example 1 is that the amount of metal salt added in step (2) is 0.082 mol. The rest is the same as that in Experimental Example 1.

[0070] Comparative Example 5 This comparative example aims to study the effect of the amount of sodium hydroxide added in step (3) on the synthesis of MOF materials.

[0071] The main difference between this comparative example and Example 1 is that the amount of sodium hydroxide added in step (3) is 0.0164 mol. The rest is the same as in Experimental Example 1.

[0072] Comparative Example 6 This comparative example aims to study the effect of the amount of sodium hydroxide added in step (3) on the synthesis of MOF materials.

[0073] The main difference between this comparative example and Example 1 is that the amount of sodium hydroxide added in step (3) is 0.082 mol. The rest is the same as in Experimental Example 1.

[0074] Performance Characterization The MOF materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for specific surface area, and the results are shown in Table 1. The testing instrument is: Mack ASAP2460.

[0075] Table 1 Group <![CDATA[Specific surface area (m 2 / g)]]> Example 1 428 Example 2 135 Example 3 152 Example 4 336 Example 5 340 Example 6 289 Comparative Example 1 87 Comparative Example 2 92 Comparative Example 3 72 Comparative Example 4 88 Comparative Example 5 85 Comparative Example 6 94 Data Analysis: (1) The method of the present invention converts waste PET plastic into a metal organic framework (MOF) material, which has an excellent porous structure, uniform pores, and a large specific surface area, showing the potential for waste resource utilization. The method of the present invention first crushes PET and mixes it with betaine, and heats it in ethylene glycol to form a ligand carrier solution; then, an alkaline earth metal salt is dissolved in DMF to prepare a metal salt solution, and NaOH is added to the ligand solution at 110-130°C to make it turbid to form a ligand salt; then, the metal salt solution is added to the ligand salt for reaction, and finally a solid-liquid mixture is obtained, which is washed and dried to obtain the target MOF material. The method is highly systematic, and the logic between the steps is clear, which ensures the quality of the product.

[0076] (2) Exploring the effects of various reaction conditions on the method of the present invention In Comparative Example 1, when the mass ratio of PET powder to betaine in step (1) is 50:1, compared with Example 1, the amount of betaine added is too little, and the performance of the MOF material deteriorates. The reason for this is analyzed as follows: residues and undegraded reaction products exist in the system, affecting the subsequent synthesis reaction process.

[0077] In Comparative Example 2, when the mass ratio of PET powder to betaine in step (1) is 4:1, compared with Example 1, the amount of betaine added is too much, and the performance of the MOF material deteriorates. The reasons are analyzed as follows: the reaction is fast, but the residual catalyst in the reaction system affects the subsequent synthesis reaction process, the prepared product contains excess impurities, and the product has large structural defects.

[0078] In Comparative Example 3, when the molar ratio of PET powder and alkaline earth metal salt in step (2) is 1:5, compared with Example 1, the amount of alkaline earth metal salt added is too small, and the performance of the MOF material deteriorates. The reasons for this are analyzed as follows: the shortage of metal salt may lead to an unsatisfactory ratio of ligand to metal ion, thereby affecting the formation of MOF and failing to fully form the desired MOF structure. At the same time, this may lead to a decrease in the yield of MOF synthesis.

[0079] In Comparative Example 4, when the molar ratio of the PET powder and the alkaline earth metal salt in step (2) is 1:5, compared with Example 1, the amount of alkaline earth metal salt added is too much, and the performance of the MOF material deteriorates. The reason is analyzed as follows: excessive addition of alkaline earth metal salt will cause the metal ions to present a non-ideal coordination state during the synthesis process, which may cause metal aggregation or precipitation instead of forming a uniform MOF structure. Excessive metal ions will produce phases or polymers different from the target MOF structure, and even cause side reactions to occur, thereby reducing the purity of the final product.

[0080] In Comparative Example 5, when the molar ratio of PET powder and sodium hydroxide in step (3) is 1:1, compared with Example 1, the amount of sodium hydroxide added is too small, and the performance of the MOF material deteriorates. The reasons are analyzed as follows: the amount of sodium hydroxide added is too small, which leads to the inability to completely catalyze the formation of the ligand salt, the reaction is incomplete, and the pore size of the finally generated MOF is uneven and the crystallinity is low.

[0081] In Comparative Example 6, when the molar ratio of PET powder to sodium hydroxide in step (3) is 1:5, compared with Example 1, the amount of sodium hydroxide added is too much, and the performance of the MOF material deteriorates. The reason for this is analyzed as follows: excessive sodium hydroxide may cause the reaction system to become too alkaline, which may inhibit the complexation reaction of the metal salt, resulting in incomplete synthesis of the desired MOF and adversely affecting the performance of the product.

[0082] In summary, the addition amount of betaine, alkaline earth metal salt and sodium hydroxide is crucial to the synthesis of metal organic framework (MOF) materials. Betaine, as an organic ligand, provides the necessary functional groups. The appropriate amount of addition can effectively promote the combination of PET and metal ions and ensure the formation of a uniform complex. The amount of metal salt directly affects the structure and function of MOF. Too much may lead to the aggregation of metal ions, while too little is not enough to form a complete structure. The addition of sodium hydroxide is used to adjust the pH of the reaction environment and promote the reaction between ligands and metal ions. Moderate alkalinity helps to generate ligand salts, but excessive amounts may cause side reactions. Therefore, controlling the addition amount of these three components is of great significance for achieving the synthesis of high-quality MOF materials and plays an important role in further improving the yield and functionality of MOF.

[0083] In the present invention, the molar amount of PET is based on its monomer.

[0084] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for converting waste plastics into high-value MOF materials based on a continuous process, characterized in that: The following steps are involved: PET powder, catalyst and ethylene glycol are mixed and heated to obtain a clear solution, then cooled to 110-130°C, sodium hydroxide is added, stirred for a primary reaction, and then a metal salt solution is added for a secondary reaction to obtain MOF material.

2. A method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 1, characterized in that: The mass ratio of PET to ethylene glycol is 1:4~10.

3. A method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 2, characterized in that: The catalyst is a weakly alkaline catalyst.

4. The method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 1, characterized in that: The heating temperature is 190-200° C., and the heating time is 2-4 hours.

5. The method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 1, characterized in that: The molar ratio of PET to sodium hydroxide is 1:2~4.

6. The method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 1, characterized in that: The stirring rate of the primary reaction is 300-800 r / min, and the time of the primary reaction is 30-60 min.

7. The method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 1, characterized in that: The metal salt is selected from alkaline earth metal salts.

8. The method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 7, characterized in that: The metal salt is selected from one or more of cobalt nitrate, nickel nitrate, zinc nitrate and calcium chloride.

9. The method for converting waste plastics into high-value MOF materials based on a continuous process as claimed in claim 1, characterized in that: The stirring rate of the secondary reaction is 300-800 r / min, and the time of the secondary reaction is 4-12 hours.

10. Use of the method according to any one of claims 1 to 9 in recycling waste plastics.

Citation Information

Patent Citations

  • Mechano-chemical method for preparing metal-organic framework material

    CN115678030A

  • Method for preparing metal-organic framework material through ball milling-solution blending

    CN115716918A

Cited By

  • Waste PET (polyethylene terephthalate)-based MOFs (metal organic frameworks) functional material as well as preparation method and application thereof

    CN121226755A